Extraoral low-level laser therapy can decrease pain but not edema and trismus after surgical extraction of impacted mandibular third molars: a randomized, placebo-controlled clinical trial - Ehsan Momeni; Farahnaz Kazemi; Parisa Sanaei-rad (BMC, 2022)
Abstract Background This study aimed to assess the effect of extraoral 940 nm low-level diode laser on pain, edema, and trismus following surgical extraction of impacted mandibular third molars. Materials and methods This split-mouth, randomized, placebo-controlled clinical trial evaluated 25 patients with bilaterally impacted mandibular third molars. One side of the jaw was randomly assigned to the laser and the other side to the control group. The laser quadrant received 940 nm diode laser irradiation (0.5 W, 10 J/cm2, continuous-wave mode, 20 s) at three points in the master muscle in contact mode immediately after surgical extraction of third molar. The third molar in the placebo quadrant was extracted after 2 weeks by the same surgeon using the same standard approach. The pain score was measured at 2 and 7 days postoperatively using a visual analog scale (VAS). To assess trismus, the distance between the incisal edges of the upper and lower central incisors was measured in maximum opening. To assess edema, the distance between the tragus and chin point was measured before and immediately after surgery and after 2 and 7 days. Data were analyzed using t-test, ANOVA, and Bonferroni test. Results The mean pain score in the first 7 days was significantly lower in the laser group (P < 0.05). Edema and trismus were the same in both groups (P > 0.05). Number of analgesics taken was significantly lower in the laser group (P < 0.05). Conclusion Single-session irradiation of 940 nm diode laser can effectively decrease pain following third molar extraction surgery. Trial registration number: IRCT20141209020258N91 on 29/12/2018.